Obsessive-Compulsive Disorder in the Elderly - Michael P. Philpot; Sube Banerjee (Behavioural Neurology)
Four cases of obsessive-compulsive disorder arising in late life in association with a presumed organic aetiology are described. Three of the four had brief episodes of OCD earlier in their lives. Neuropsychological assessment demonstrated impairments in verbal fluency and visuo-spatial tasks. No case exhibited global intellectual impairment. The two patients who complied with appropriate treatment became asymptomatic after 4–6 months.